Management of carotid stenosis - Spence, J. David (Henry Stewart Talks, 2017)
Benefit of carotid endarterectomy (CEA), Symptomatic & Asymptomatic carotid stenosis and their treatment, Treatment of symptomatic severe stenosis with special features, Identifying prospective benefit from intervention, Carotid plaque area as predictor of events, Treating arteries instead of risk factors, Intensive medical therapy